2006
DOI: 10.1002/pds.1316
|View full text |Cite
|
Sign up to set email alerts
|

Trends in consumption of psychiatric drugs in Serbia and Montenegro 2000–2004

Abstract: The total consumption of psychiatric drugs significantly increased. The utilization of anxiolytic/hypnotic drugs in 2004 reached 60 DDDs/1000 inhabitants/day, which is in collision with the trend in developed countries. It is necessary to form national guidelines for prescribing anxiolytic/hypnotic drugs, in order to rationalize their use. More favourable is the antidepressant (SSRIs in particular) and atypical antipsychotic drugs utilization increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 3 publications
1
17
1
1
Order By: Relevance
“…Regarding the issue of incomplete data, it is interesting to observe that, for example, our findings on anxiolytic and antipsychotic drug use in Serbia do not support the findings of a previous study that showed a considerably lower consumption of these two drug classes [ 21 ]. This inconsistency may be related to the use of different data sources and providers.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the issue of incomplete data, it is interesting to observe that, for example, our findings on anxiolytic and antipsychotic drug use in Serbia do not support the findings of a previous study that showed a considerably lower consumption of these two drug classes [ 21 ]. This inconsistency may be related to the use of different data sources and providers.…”
Section: Discussioncontrasting
confidence: 99%
“…The first episode of depression occurred 9 years prior to the current (2-15 years); the average number of hospitalizations was 2 (1)(2)(3)(4). Patients with the other diagnoses were similar to the unipolar depression group in terms of sociodemographic and clinical parameters (47.6 ± 10.9 years of age, p = 0.07; females 56%, p = 0.11; high school 54.1%, p = 0.96; first diagnosis 8 years prior to the current study (3-16 years), p = 0.70; the number of hospitalizations 2 (1-4), p = 0.10)).…”
Section: Resultsmentioning
confidence: 99%
“…The use of antidepressants (ADs) has been steadily increasing during the last decade 1,2 . Drugs from this group act predominantly on serotonergic and/or noradrenergic transmission and reduce a spectrum of symptoms -from affective and will-instinctive to cognitive psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…3,[5][6]24 Noutros países, as benzodiazepinas mais prescritas são o diazepam (Sérvia e Montenegro, Austrália) e o lorazepam (Canadá). [25][26] Pouco se pode inferir acerca da qualidade da prescrição a nível populacional sem informações sobre o motivo da prescrição e a prevalência da(s) doença(s) as- sociada(s). 15 A codificação de diagnósticos no SAM não ocorre ainda de modo uniforme, pelo que não se pode relacionar a prescrição de fármacos com a prevalência de patologias baseada na codificação.…”
Section: Discussionunclassified